2021
DOI: 10.1371/journal.pone.0246168
|View full text |Cite
|
Sign up to set email alerts
|

A novel mouse model for checkpoint inhibitor-induced adverse events

Abstract: Immune checkpoint inhibitors have demonstrated significant efficacy in the treatment of a variety of cancers, however their therapeutic potential is limited by abstruse immune related adverse events. Currently, no robust animal model exists of checkpoint inhibitor-induced adverse events. Establishing such a model will improve our mechanistic understanding of this process, which in turn will inform design of improved therapies. We developed a mouse model to determine inflammatory toxicities in response to dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 39 publications
0
59
0
Order By: Relevance
“…A primary consideration in the development of strategies to reduce IrAE must be the preservation of anti-cancer effects of ICI. Early efforts using glucocorticoids for IrAE treatment inconsistently reversed autoimmunity or compromised anti-cancer effects 5,19 . In addition, previous studies have shown reduction of thyroid IrAE by elimination of CD4 + T cells 26 , but this is not readily translatable to cancer patients given the importance of CD4 + T cells in cellmediated immunity 36,68 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A primary consideration in the development of strategies to reduce IrAE must be the preservation of anti-cancer effects of ICI. Early efforts using glucocorticoids for IrAE treatment inconsistently reversed autoimmunity or compromised anti-cancer effects 5,19 . In addition, previous studies have shown reduction of thyroid IrAE by elimination of CD4 + T cells 26 , but this is not readily translatable to cancer patients given the importance of CD4 + T cells in cellmediated immunity 36,68 .…”
Section: Discussionmentioning
confidence: 99%
“…While prior studies have reported autoimmunity in ICI-treated mice, these models on the C57BL/6 (B6) background developed minimal ICI-IrAEs. Augmenting these mild phenotypes required significant manipulation, such as regulatory T cell depletion , genetic knock-in of human checkpoint proteins 24 , chemical stimulants 25 or co-administration of complete Freund's adjuvant 19 .…”
Section: The Nod Background Strain Predisposes Mice To Ici-iraes That Mimic Those Seen In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, while ILICI shares some features of autoimmune hepatitis (AIH), the number of plasma cell infiltrates in this study was far less than what is seen in classic AIH 116 . In animal models of ICIs both CD4 + and CD8 + T cells infiltrates have been noted in the liver 117 . Johncilla et al.…”
Section: Immune-mediated Liver Injury Caused By Checkpoint Inhibitors (Ilici)mentioning
confidence: 99%
“…This finding strongly suggests that NR2F6 might be an inducible and thus highly localized immune checkpoint at the tumor site. Of note, and in stark contrast, mice treated with a combination of anti-mouse PD-1 and CTLA-4 antibodies have been reported to develop severe diseases characterized by organ infiltration of immune cells [ 64 ].…”
Section: Beyond Current Immune Checkpoint Therapiesmentioning
confidence: 99%